Identifying clinical measures that most accurately reflect the progression of disability in Parkinson disease. (April 2016) - Ellis, Terry D.; Cavanaugh, James T.; Earhart, Gammon M.; Ford, Matthew P.; Foreman, K. Bo; Thackeray, Anne; Thiese, Matthew S.; Dibble, Leland E.
Abstract: Introduction: The temporal relationship between disease and disability progression in Parkinson disease (PD) is not well understood. Our objective was to describe the natural, multidimensional trajectory of disability in persons with PD over a two-year period. Methods: We conducted a multi-center, prospective cohort study involving four institutions. Data were collected at baseline and at 6-month intervals over 2 years using standardized clinical tests representing three World Health Organization defined disability domains: impairment, activity limitation, and participation restriction. Unadjusted mixed effects growth models characterized trajectories of disability in the three disability domains. The data set was analyzed using restricted maximum likelihood (REML) estimation. Standardized estimates of change were also computed using Cohen's d for each measure. Results: Of the 266 enrolled participants, we analysed data from individuals who participated in at least 3 assessments (n = 207, 79%). Rates of disability progression over the 2-year period differed across domains. Moderate effects were detected for motor impairment (d = .28) and walking-related activity limitation (gait-related balance (d = .31); gait speed (d = .30)). Marginal effects were noted for upper extremity-related activity limitation (d = .11) and health-related quality of life participation restriction (d = .08). Conclusions: The natural trajectory of walking-related activity limitation was the most potent indicator of evolving disability, suggesting that routine assessment of walking and periodic rehabilitation is likely to be warranted for many persons with PD. Natural trajectories of disability provide important comparison data for future intervention studies. Highlights: Various dimensions of disability declined at distinct rates over 2-years in PD. The steepest declines occurred in gait, gait-related balance and motor impairments over a 2-year period. Declines in gait speed and gait-related balance are important markers of disability. Early treatment to reduce gait related disability in PD is warranted.